حساب السعة التخزينية الحالية وحجم الرسوبيات في بحيرة سد 16 تشرين باللاذقية بالطرائق الطبوغرافية - بوبو, معن (Latakia University Journal -Engineering Sciences Series, 2019)
حساب السعة التخزينية الحالية وحجم الرسوبيات في بحيرة سد 16 تشرين باللاذقية بالطرائق الطبوغرافية معن بوبو في ظل النقص في كميات الأمطار أو في الموارد المائية وكلف بناء سدود جديدة فإنه يتوجب العمل على زيادة كفاءة السدود المقامة حاليا، وإطالة عمرها الزمني، ومعرفة سعتها التخزينية الفعلية، لتضع حقيقة الوضع أمام صناع القرار. حيث أنه مع كل الدراسات التي تجري قبل تنفيذ السد لابد من حساب كمية الرسوبيات المتراكمة في البحيرة بعد تشغيل السد للتأكد من دقة حسابات حركة الرسوبيات. أهداف المسح الأولي للبحيرة هي: توثيق سعة التخزين المائية الحالية، مقدار الفاقد من حجم التخزين بسبب تراكم الرسوبيات، مواقع ومعدل تخزين الرسوبيات. وصل البحث إلى نتائج حول كميات ومواقع حت الضفاف، وكميات ومواقع الترسيب وصولاً إلى حساب كمية الرسوبيات النهائية أو الفاقد في حجم التخزين وهو 12,382,930m3 In light of the shortage of rainfall or water resources and the costs of building new dams, this requires increasing the efficiency of the existing dams, prolonging its time-life and knowing its actual storage capacity, thus putting the situation in the hands of decision-makers. As with all studies conducted before the implementation of the dam the amount of sediment accumulated in the reservoir must be calculated after putting the dam in service to ensure the accuracy calculations of sediment movement. The primary objectives of the reservoir survey were to document the present water storage capacity, loss of storage from sediment accumulation, rate and location of sediment deposits. The research concluded results on the quantities and locations of the erosion of banks, and the quantities and locations of the sedimentation to the calculation of the amount of final sediments or losses in the volume of storage which is 12,382,930m3